Legal Review of The Granting of Remission to Prisoners in Class II A Langkat Prison - Christian Carlos Partogi Siahaan; Syaiful Asmi Hasibuan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The rights of prisoners as Indonesian citizens who have lost their independence due to committing a criminal offence, must be carried out in accordance with human rights. One of the rights of prisoners is to get a reduction in the period of punishment (remission) which is regulated in the legislation. Remission in the implementation system of imprisonment, especially concerning coaching issues, is recognised and protected by law. This study aims to determine the legal basis for granting remission to prisoners, to determine the implementation of granting remission to prisoners in the Class II A Langkat Narcotics Penitentiary and to determine the obstacles and solutions in the implementation of granting remission to prisoners in the Class II A Langkat Narcotics Penitentiary. The research method used in this research is descriptive with the type of empirical legal research or field research and qualitative data analysis. The legal basis for granting remission for prisoners is regulated in Law Number 22 of 2022 concerning Corrections and several implementing regulations. In these regulations, remission for prisoners can be given to prisoners who meet certain conditions. The stages of granting remission by submitting an application accompanied by evidence that he meets the requirements, the correctional institution will verify and evaluate the application, after the verification and evaluation process is complete, the correctional institution will make a decision on whether the inmate is entitled or not to receive remission. The rules for obtaining remission in Indonesia should be tightened and reinforced in accordance with the applicable law without any misappropriation and intensive socialisation, training for officers, effective cooperation with authorities such as the police, prosecutors and judges and the information provided about the procedures for granting remission is correct and precise.